Cardiopulmonary effects of xylazine- ketamine hydrochloride and acepromazine- ketamine hydrochloride combinations in dogs - Celal İzci; Mursayettin Eksen; Yılmaz Koç; Ercan Keskin; Sırrı Avki; Mehmet Gören (Eurasian Journal of Veterinary Sciences)
This study was carried out in two groups that consists of 5 dogs. Cardiopulmonary function was as sessed in healty do gs that given xylazine- .ketamine hydrochloride and acepromazine- ketamine hydrochloride combinations intramuscu!arly. Arterfal blood pressure, heart rate and potassium demonstrated significant alterations statistica!!y from pretest values. Arterial blood press u re (systolic, diastolic and me an) was significantly decreased by bath combinations. The xylazine- ketamine hydroch!oride combination decreased the he art rat e 26.5 % in ratio, where as the acepromazine- ketamine hydrochloride combination increased it a maximum of % 67. 1. The respiratory rate, body temperature, arterfal pH, PaCO2 PaO2 calcium and sodium values were not significantly altered.